Harnessing Human Dendritic Cell Subsets for Medicine - Ueno, Hideki (2010)
Immunity results from a complex interplay between the antigen-nonspecific innate immune system and the antigen-specific adaptive immune system. The cells and molecules of the innate system employ non-clonal recognition receptors including lectins, Toll-like receptors, NOD-like receptors and helicases. B and T lymphocytes of the adaptive immune system employ clonal receptors recognizing antigens or their derived peptides in a highly specific manner. An essential link between innate and adaptive immunity is provided by dendritic cells (DCs). DCs can induce such contrasting states as immunity and tolerance. The recent years have brought a wealth of information on the biology of DCs revealing the complexity of this cell system. Indeed, DC plasticity and subsets are prominent determinants of the type and quality of elicited immune responses. Here we summarize our recent studies aimed at a better understanding of the DC system to unravel the pathophysiology of human diseases and design novel human vaccines.